Effects of a Multifunctional Cover Crop (LivinGro®) on Soil Quality Indicators in Zaragoza, Spain - Javier González-Pérez; José Antonio Sillero-Medina; Paloma Hueso-González; José Damián Ruiz-Sinoga; Francisco Javier Peris-Felipo; Ana Lia Gayán-Quijano (Land)
Soil degradation is a significant threat to agricultural systems and contemporary societies worldwide, especially in the context of climate change. Proper management of agricultural systems is a priority for maintaining food security and achieving sustainable development. It is therefore important to assess the efficacy of different interventions that are designed to improve the quality of agricultural soils. Measurements of physical, chemical, and biological indicators of soil quality can be used to examine the efficacy of strategies or methods that were designed to prevent soil degradation. We measured seven physicochemical indicators of soil quality at a representative experimental plot of nectarines in the province of Zaragoza (Spain) over three years (2020–2023) and compared the effect of a multifunctional cover crop (LivinGro® MCC, Basel, Switzerland) with conventional treatment (control) on soil quality. Soil samples were collected every two months from the treelines and inter-rows (paths for farming vehicles). In general, the MCC zones in the treelines and inter-rows had better soil health, especially in key indicators such as basal soil respiration, organic matter, nitrogen, and porosity. Climatic variability, especially seasonal differences in rainfall, also affected multiple soil indicators. During many sample periods, the MCC zones of the treelines and inter-rows had significantly increased soil organic matter, basal respiration, total nitrogen, nitrate, total porosity, and available water content, but the MCC and control zones had no significant differences in bulk density. The differences between the MCC zones and control zones, especially in basal soil respiration, were greater during the wet seasons. Our results indicate that the LivinGro® MCC prevented degradation of agricultural soils in a region with a continental Mediterranean climate.